PENAFSIRAN KIAI BANYUWANGI TERHADAP SURAH AL-FATIHAH: Studi Kenaskahan atas Manuskrip Tafsir Al-Qur’an Al-Karim Berbahasa Indonesia Karya KH. Suhaimi Rofiuddin - Muhamad Asadulloh (QOF, 2021)
The article philologically analyses the text in the interpretation of Surah Al Fatihah by KH. Suhaimin Rofiudin (1919-1982) entitled Tafsir Al-Qur’an Al Karim Berbahasa Indonesia. It reveals how the biography reconstruction of Suhaimi Rofi’uddin who was the author of Surah al-Fatihah interpretation manuscript. This study is about how to provide a philological reconstruction of Suhaimi’s manuscript history. Third, this research discusses how the text of the manuscript was influenced by some factors. By using the philological approach in the step of searching for supporting data, also using ‘ulum al-Qur’an as an analysis of the method used by the scriptwriter to understand Surah Al-Fatihah, in addition, to use the discourse of Foucault also serves as an auxiliary tool to examine the history of the rules of interpretation used by the author. From Suhaimi’s understanding, the interpretation of Surah al-Fatihah doesn’t same with the earlier interpretation which discusses about the spiritual tradition of Qurisy tribe, but Suhaimi’s manuscript is about West hegemony. This textual image is caused by the factor of Suhaimis’s contextual background about Holland colonialitation and the Six-Day war between Arab and Israel.